2021
DOI: 10.1093/alcalc/agaa147
|View full text |Cite
|
Sign up to set email alerts
|

Digital Interventions for People With Co-Occurring Depression and Problematic Alcohol Use: A Systematic Review and Meta-Analysis

Abstract: Aims This systematic review and meta-analysis assessed the effectiveness of digital interventions addressing depressive symptoms and alcohol use simultaneously among people with co-occurring depression and problematic alcohol use. Methods Seven databases were searched for trials evaluating digital interventions aimed at depression and alcohol use. Random-effects meta-analyses were conducted to pool effects on depressive sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
0
16
2
Order By: Relevance
“…These results are in contrast with the limited existing evidence base indicating that digital interventions for combined depression and drinking can reduce alcohol consumption and improve symptoms of depression among people with these co-occurring conditions ( Schouten et al, 2021 ). Why might the results from this trial differ?…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…These results are in contrast with the limited existing evidence base indicating that digital interventions for combined depression and drinking can reduce alcohol consumption and improve symptoms of depression among people with these co-occurring conditions ( Schouten et al, 2021 ). Why might the results from this trial differ?…”
Section: Discussioncontrasting
confidence: 91%
“…A smaller but active area of Internet intervention research involves the design and evaluation of interventions that address both depression and hazardous alcohol use simultaneously. A recent systematic review and meta-analysis of randomized controlled trials (RCT) of combined digital interventions for co-occurring hazardous alcohol use and depression found evidence for the positive impact of these interventions on improvements in symptoms of depression at three-month follow-up and on reductions in alcohol consumption at six-month follow-up ( Schouten et al, 2021 ). However, the research base is limited, with only six trials included in the review and with insufficient studies to separate the research that targeted people in treatment from those which recruited people with co-occurring disorders outside of clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…A sub-group meta-analysis from 2014, restricted to exclusively MI/CBT-based interventions, showed digital MI/CBT interventions may even reduce depression outcomes to a larger extent than face-to-face MI/CBT treatment in adults with co-occurring depression and problematic alcohol use [18]. Our recent systematic review with meta-analysis on digital interventions for cooccurring depression and problematic alcohol use also provides preliminary evidence of the small but significant positive effects of digital interventions on reducing depressive symptoms after 3-month follow-up (g = 0.34) and alcohol use after 6-month follow-up (g = 0.14) [48]. Digital interventions seem therefore particularly promising for this comorbid population.…”
Section: Introductionmentioning
confidence: 90%
“…Digital interventions seem therefore particularly promising for this comorbid population. However, these meta-analytic findings are limited by high risk of bias ratings for all included studies, small amount of included studies with sometimes small sample sizes and differences with regards to digital intervention and population characteristics [48]. Furthermore, only two trials were conducted among younger populations and report mixed findings [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…However, internet-based interventions that have integrated CBT and MI content designed to target all symptoms simultaneously have only emerged recently. A recent systematic review and meta -analysis of the literature examined the effects of online interventions for comorbid alcohol use and depression ( Schouten et al, 2021 ). Of the six studies that met inclusion criteria, they found small significant pooled effects for depression at 3-months ( g = 0.34) but not at the 6-month follow up, and small significant effects for alcohol at 6-month follow-up ( g = 0.14) but not 3-months.…”
Section: Introductionmentioning
confidence: 99%